An Architecture for Anonymous Mobile Coupons in a Large Network. (18th December 2016) - Bartoli, Alberto; Medvet, Eric
Abstract : A mobile coupon (m-coupon) can be presented with a smartphone for obtaining a financial discount when purchasing a product or a service. M-coupons are a powerful marketing tool that has enjoyed a huge growth and diffusion, involving tens of millions of people each year. We propose an architecture which may enable significant improvements over current m-coupon technology, in terms of acceptance of potential customers and of marketing actions that become feasible: the customer does not need to install any dedicated app; an m-coupon is not bound to any specific device or customer; an m-coupon may be redeemed at any store in a set of potentially many thousands of stores, without any prior arrangement between customer and store. We are not aware of any proposal with these properties.